Assessment of preparedness and proficiency in basic and advanced life support among nursing professionals: a cross-sectional study - Izquierdo-Condoy, Juan S.; Arias Rodríguez, Fabián D.; Duque-Sánchez, Erick; Alegría N., Nicolás; Rojas Cadena, Marlon; Naranjo-Lara, Patricio; Mendoza, Alexander Puglla; Jima-Sanmartín, Jackson; Casanova, Dayana Andrade; García, Balbina; Giraldo, Natalia Castaño (Frontiers in Medicine, 2024)
Background: Cardiac diseases are among the leading causes of death worldwide, including sudden cardiac arrest in particular. Nursing professionals are often the first to encounter these scenarios in various settings. Adequate preparation and competent knowledge among nurses significantly impact survival rates positively.To describe the state of knowledge about Basic and Advanced Life Support guidelines among Ecuadorian nursing professionals.Methodology: A nationwide, descriptive, cross-sectional study was conducted from February to April 2023 among Ecuadorian nursing professionals. Participants were invited through official social media groups such as WhatsApp and Facebook. The study utilized a self-administered online questionnaire to evaluate theoretical knowledge of Basic Life Support (BLS) and Advanced Life Support (ALS). Knowledge scores were assigned based on the number of correct answers on the tests. T-tests and oneway ANOVA were used to examine relationships between knowledge scores and demographic and academic training variables.Results: A total of 217 nursing professionals participated in the study. The majority of the participants were female (77.4%) and held a university degree (79.9%). Among them, only 44.7% claimed to have obtained a BLS training certificate at least once, and 19.4% had ALS certification. The overall BLS knowledge score (4.8/10 ± 1.8 points) was higher than the ALS score (4.3/10 ± 1.8 points). Participants who had obtained BLS certification and those who used evidence-based summaries as a source of extracurricular training achieved higher BLS and ALS knowledge scores.Ecuadorian nursing professionals in this study exhibited a significant deficiency in theoretical knowledge of BLS and ALS. Formal training and preparation positively impact life support knowledge. Support and inclusion of Ecuadorian nurses in training and academic preparation programs beginning at the undergraduate level are essential for promoting life support knowledge and improving outcomes.